ANALYSIS OF THE EFFECT OF MARKETING MIX ON CUSTOMER SATISFACTION AT JEUNIEB CITY COFFEE IN JEUNIEB SUB-DISTRICT, BIREUEN REGENCY - T. Edyansyah; Rico Nur Ilham; Muhammad Roni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The purpose of this study was to determine the effect of marketing mix on customer satisfaction at Jeunieb City Coffee in Jeunieb Sub-District, Bireuen Regency. This study used quantitative methods, the population in this study were customers who visited Jeunieb City Coffee. The sample in this study amounted to 75 respondents, as for the data collection technique used, namely questionnaires, the author distributed questionnaires to 75 customers of Jeunieb City Coffee. The results showed that the seven independent variables, namely Product (X1) has a calculated value (5,880) > ttable (1,993), Price (X2) has a calculated value (4,054) > ttable (1,993), Place (X3) has a calculated value (4,514) > ttable (1,993), Promotion (X4) has a calculated value (3,386) > ttable (1,993), People (X5) have a tcount value (5,920) > ttable (1,993), Process (X6) has a tcount value (3,335) > ttable (1,993), Physical Evidence (X7) has a calculated value (6,200) > ttable (1,993). So it can be concluded that the seven independent variables have a positive effect on customer satisfaction at Jeunieb City Coffee in Jeunieb District, Bireuen Regency.